MARRIED BY ACCIDENT PONOROGO DI MASA PANDEMI: FAKTOR, HUKUM DAN SOLUSI ALTERNATIF - Munawwir Ramadhan; Dina Sakinah Siregar (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2022)
Recently, there are various bad deeds. They make you close to fornicate. Those are not strange anymore now. We can find many cases of married by accident in Ponorogo even we get datas show 8 times as numerous cases in 2021 than 2019. The Society Psychology condition is really bad and Free social gathering becomes the factor especially in adolescent. In society, doing a marriage for woman pregnant from fornicate is an alternative because the deed should not happen. But there are various different opinions about it. This article uses empiric and sociologic research. The method is qualitative-descriptive. It will analyze, discuss, understand, and opinion from researcher. It uses Islamic and civil law as the main literature. It takes library research and content analyzing. This research discusses about laws of married by accident the factors and the solutions for Ponorogo society. The result gives the thoughts for the solution accident and minimize it more.